Postbiotics: From emerging concept to application - Aggarwal, Sunita; Sabharwal, Vandana; Kaushik, Pragya; Joshi, Anushka; Aayushi, Aayushi; Suri, Manjula (Frontiers in Sustainable Food Systems, 2022)
The microbiome innovation has resulted in an umbrella term, postbiotics, which refers to nonviable microbial cells, metabolic byproducts and their microbial components released after lysis. Postbiotics, modulate immune response, gene expression, inhibit pathogen binding, maintain intestinal barriers, help in controlling carcinogenesis and pathogen infections. Postbiotics have antimicrobial, antioxidant, and immunomodulatory properties with favourable physiological, immunological, neuro-hormonal, regulatory and metabolic reactions. Consumption of postbiotics relieves symptoms of various diseases and viral infections such as SARS-CoV-2. Postbiotics can act as alternatives for pre-probiotic specially in immunosuppressed patients, children and premature neonates. Postbiotics are used to preserve and enhance nutritional properties of food, elimination of biofilms and skin conditioning in cosmetics. Postbiotics have numerous advantages over live bacteria with no risk of bacterial translocation from the gut to blood, acquisition of antibiotic resistance genes. The process of extraction, standardisation, transport, and storage of postbiotic is more natural. Bioengineering techniques such as fermentation technology, high pressure etc., may be used for the synthesis of different postbiotics. Safety assessment and quality assurance of postbiotic is important as they may induce stomach discomfort, sepsis and/or toxic shock. Postbiotics are still in their infancy compared to pre- and pro- biotics but future research in this field may contribute to improved physiological functions and host health. The current review comprehensively summarises new frontiers of research in postbiotics.